24=61-h

Simple and best practice solution for 24=61-h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=61-h equation:


Simplifying
24 = 61 + -1h

Solving
24 = 61 + -1h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add 'h' to each side of the equation.
24 + h = 61 + -1h + h

Combine like terms: -1h + h = 0
24 + h = 61 + 0
24 + h = 61

Add '-24' to each side of the equation.
24 + -24 + h = 61 + -24

Combine like terms: 24 + -24 = 0
0 + h = 61 + -24
h = 61 + -24

Combine like terms: 61 + -24 = 37
h = 37

Simplifying
h = 37

See similar equations:

| 88-w=11 | | 7(b+2)=49whatisb | | 18x^2+51x+21=0 | | 42=e-7 | | 9-3k=17-k | | -6-(-9)/3 | | 84/280= | | (2x+4)dx+(3y-1)dy=0 | | 16w=7w+27 | | (2/5x)(5y)(-2x)= | | 2.5-y= | | y=(5-3x)/(7-4x) | | 6-3x-2=-4x | | t-42=24 | | x=(5-3y)/(7-4y) | | 59=k-4 | | 5(a^2)+6a-8=0 | | 4=62-e | | X+11v+4x-v= | | 79-x=1 | | 60-x=41 | | 11+5z=6 | | 4=87-y | | (4y^2)+3y-1=0 | | (5x-9)(9x+8)=0 | | 90-m=1 | | 96-p=63 | | (9k^2)-9k+2=0 | | 26t+5a-4t-2= | | r-28=33 | | 84-v=29 | | (7z^2)-10z+3=0 |

Equations solver categories